Study of enteric pathogens among children in the tropics and effects of prolonged storage of stool samples. (25th March 2021) - Schotte, U.; Hoffmann, T.; Schwarz, N.G.; Rojak, S.; Lusingu, J.; Minja, D.; Kaseka, J.; Mbwana, J.; Gesase, S.; May, J.; Dekker, D.; Frickmann, H.
Abstract: The study was performed to compare real‐time PCR after nucleic acid extraction directly from stool samples as well as from samples stored and transported on Whatman papers or flocked swabs at ambient temperature in the tropics. In addition, the possible suitability for a clear determination of likely aetiological relevance of PCR‐based pathogen detections based on cycle threshold (Ct) values was assessed. From 632 Tanzanian children <5 years of age with and without gastrointestinal symptoms, 466 samples were subjected to nucleic acid extraction and real‐time PCR for gastrointestinal viral, bacterial and protozoan pathogens. Equal or even higher frequencies of pathogen detections from Whatman papers or flocked swabs were achieved compared with nucleic acid extraction directly from stool samples. Comparison of the Ct values showed no significant difference according to the nucleic acid extraction strategy. Also, the Ct values did not allow a decision whether a detected pathogen was associated with gastrointestinal symptoms. Abstract : Significance and Impact of the Study: Real‐time PCR is a reliable tool even after long‐term storage and transport of samples on Whatman papers or flocked swabs. Unfortunately, Ct value assessment does not allow a decision whether a detected pathogen in stool is aetiologically relevant.